Fiscal consolidation and unemployment: does EPL matter? A look at EU countries - Alessandro Turrini (IZA Journal of Labor Policy, 2013)
This paper estimates the impact of fiscal consolidation on unemployment and job market flows across EU countries using a recent database of consolidation episodes built on the basis of a 'narrative' approach (Devries et al., 2011). Results show that the impact of fiscal consolidation on cyclical unemployment is temporary and significant mostly for expenditure measures. As expected, the impact of fiscal policy shocks on job separation rates is much stronger in low-EPL countries, while for high-EPL countries there is a stronger reduction in the rate at which new jobs are created. Since a reduced job-finding rate corresponds to a longer average duration of unemployment spells, fiscal policy shocks also tend to have a stronger impact on long-term unemployment if EPL for permanent contracts is stricter.
Keywords: E62; J63; J65; 330; Fiscal consolidation; Unemployment; Job market flows; Employment protection legislation; Labour market reforms